Treatment of multiple myeloma with immunomodulatory drugs – thalidomide, lenalidomide and pomalidomide - Rzepecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2009)
Multiple myeloma (MM) is a disease of plasma cells that has fatal consequences. New insights into the biology of MM have identified molecular mechanisms that hold promise as therapeutic targets. Laboratory and preclinical studies have shown that intracellular regulatory proteins and functional interactions between MM cells and the bone marrow microenvironment have a pivotal role in the growth, survival, drug resistance, and malignant progression of MM cells. IMiDs are structural and functional analogues of thalidomide that represent a promising new class of immunomodulators for treatment of a variety of inflammatory, autoimmune, and neoplastic diseases. The second-generation IMiDs, such as lenalidomide and pomalidomide, exhibited a greatly enhanced potency for immunomodulation and anti- -angiogenesis when compared with the parent compound, thalidomide. These new agents associated with molecular targets have prompted clinical investigators to design new treatment strategies initially for advanced MM and later for newly diagnosed multiple myeloma, with encouraging preliminary results.